Pendidikan Akhlak Berbasis Filsafat Ilmu Islam: Telaah Penalaran Bayani, Irfani, Dan Burhani Pada Jenjang Dasar - hikmah puspasari; Usman (Advances In Education Journal, 2025)
Moral education plays an important role in shaping the character and morals of students, especially at the elementary level, where these values ​​begin to be intensively instilled. However, current challenges demand an approach that is able to integrate Islamic values ​​comprehensively. This article aims to examine how the integration of Islamic epistemological reasoning, namely bayani, irfani, and burhani, can be the basis for developing a more comprehensive and applicable moral education method. The method used is a literature study with a systematic qualitative approach through literature review and content analysis. The results of the study show that the combination of these three approaches is able to form a moral education model that is not only based on religious texts, but also combines spiritual and rational aspects so as to help form humans who are noble, critical, and have high spiritual awareness. Therefore, it is recommended that moral education at the elementary level adopt this integrative model so that it is able to adapt to the development of the times while maintaining Islamic values ​​as a whole.